Outdoor Study Approach in Strengthening Science Learning Among Elementary Students: Pendekatan Outdoor Study dalam Penguatan Pembelajaran Sains pada Siswa Sekolah Dasar - Fika Andriani; Apdoludin Apdoludin; Aldino Aldino (Academia Open, 2025)
General Background: Science and Social Science (IPAS) learning in elementary schools often shows low engagement and achievement due to monotonous classroom-centered approaches. Specific Background: At SD Negeri 071/II Sungai Gambir, many students relied passively on teacher explanations and demonstrated limited participation. Knowledge Gap: Conventional methods were unable to foster active involvement and meaningful understanding of scientific concepts. Aim: This study explored the use of the outdoor study approach to strengthen the science learning process and outcomes of fourth-grade students. Results: Conducted as classroom action research in two cycles with 17 students, findings indicated consistent improvement. Teacher performance rose from 72.22% to 88.88%, student activity increased from 70.58% to 88.23%, and cognitive achievement improved from 52.94% to 88.23%. Novelty: Unlike prior works, this study integrated outdoor study with structured peer tutoring and visual media to optimize learning within limited timeframes. Implications: The results demonstrate that outdoor study can cultivate active participation, deeper conceptual understanding, and higher achievement in science learning at the elementary level. Highlights: Outdoor study increased teacher performance, student activity, and learning outcomes. Visual media and peer tutoring enhanced learning during outdoor sessions. Findings show outdoor study creates meaningful and enjoyable science learning. Keywords: Outdoor Study, Science Learning, Student Engagement, Classroom Action Research, Elementary Education